2019
DOI: 10.1016/j.jallcom.2018.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the role of defects on the magnetic response and the structural, electronic and hyperfine properties of ZnFe2O4

Abstract: Ab initio study of the role of defects on the magnetic response and the structural, electronic and hyperfine properties of ZnFe 2 O 4 . `

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…For both O 4 -Fe 4 and O 4 -Fe 4 -O 4 terminations no spin-polarization was found at the Zn-sites while spin-polarization in the order of 0.15 μ B was found for some oxygen atoms (a similar result was obtained in reduced ZnFe 2 O 4 , see Ref. [36]).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…For both O 4 -Fe 4 and O 4 -Fe 4 -O 4 terminations no spin-polarization was found at the Zn-sites while spin-polarization in the order of 0.15 μ B was found for some oxygen atoms (a similar result was obtained in reduced ZnFe 2 O 4 , see Ref. [36]).…”
Section: Resultsmentioning
confidence: 59%
“…A similar effect was found in reduced bulk ZnFe 2 O 4 . In this case, the formation of an oxygen vacancy reduce the magnitude of the magnetic moments of the three Fe atoms nearest neighbors to the vacancy sites to from 4.2 μ B [17] to 4.0 μ B Fe atoms) and −3.6 μ B for the remaining one [36]. The Fe atoms located in layers 2.3 Å (at least) below the surface present magnetic moments in the order of 4.1-4.2 μ B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An antiferromagnetic spin arrangement ( Figure S1) was found to correspond to the lowest energy, which is in consistent with reported results. 47,48 The synthesized ZnFe 2 O 4 catalyst was imaged via scanning tunneling electron microscopy (STEM). 49,50 The HAADF-STEM image ( Figure 1) revealed that in perpendicular sections the two in plane directions are [110] and [001], which indicates that the sample was inspected from the [110] direction.…”
Section: Znfe 2 O 4 Surfaces: Structures and Stabilitymentioning
confidence: 99%